2018
DOI: 10.1093/femsec/fiy041
|View full text |Cite|
|
Sign up to set email alerts
|

Antibiotic resistance genes show enhanced mobilization through suspended growth and biofilm-based wastewater treatment processes

Abstract: Wastewater treatment plants (WWTPs) are known to harbor antibiotic resistance genes (ARGs) that are disseminated into the environment via effluent. However, few studies have compared abundance, mobilization and selective pressures for ARGs in WWTPs as a function of variations in secondary treatment bioprocesses. We used shotgun metagenomics to provide a comprehensive analysis of ARG composition, relationship to mobile genetic elements and co-occurrences with antibiotic production genes (APGs) throughout two fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Thus, a concentration effect within the system is a possible explanation for the presence of tetracycline-resistant bacteria in the treated water. In contrast, however, a recent study that compared abundances of ARGs in activated sludge and a trickling filter suggested that there is no difference in the prevalence of ARG mobilization in the treated effluents (Petrovich et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, a concentration effect within the system is a possible explanation for the presence of tetracycline-resistant bacteria in the treated water. In contrast, however, a recent study that compared abundances of ARGs in activated sludge and a trickling filter suggested that there is no difference in the prevalence of ARG mobilization in the treated effluents (Petrovich et al, 2018 ).…”
Section: Discussionmentioning
confidence: 95%
“…Such mobilization of ARGs persisting in a WWTP effluent biofilm was suggested to pose a risk of dissemination to receiving waterbodies as the relative abundance of ARGs associated with MGEs, which in system's effluent reached up to 82% (Petrovich et al . 2018 ) and differed based on the MGE type respect to river biofilms (Balcázar, Subirats and Borrego 2015 ). Numerous in vitro studies demonstrated that sub-inhibitory doses of some antibiotics are sufficient to specifically induce the switch from planktonic to biofilm forming phenotype of bacteria (Hoffman et al .…”
Section: Metagenomics To Address Environmental Amr Detectionmentioning
confidence: 99%
“…Certain natural and anthropic environments could supply optimal conditions for natural transformation. An example are biofilms in which cell density is very high and cells can be exposed to high concentrations of free DNA (even higher than the ones routinely used in laboratory procedures) derived from the dead neighboring cells (Baur et al, 1996;Hasegawa et al, 2018); this condition can result in ARGs acquisition and spread in the bacterial communities, as characterized in several studies (Petrovich et al, 2018). Moreover, clinically relevant ARGs enter freshwater systems through the outflow of WWTPs (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%